Analisis Risiko Pada Proyek Konstruksi Pembangunan Gedung Negara Imigrasi Kelas III Non TPI Di Kota Kediri dengan Menggunakan Metode House Of Risk (Jurnal Spesialis Teknik Sipil (JSpTS), 2023)
Risk analysis is important in government-funded projects. This research was conducted to determine the risks faced in the construction project of the Non-TPI Class III Immigration State Building in Kediri City. The purpose of this study is to determine the impact of risk by identifying it at the implementation stage, and analyzing risk responses in order to reduce risk. The data analysis used in this study is an analysis using the House of Risk method. Besides that, Mean Analysis and Frequency Analysis will also be used. After processing the data at the house of risk phase 1, 7 priority risk agents were obtained, namely poor project management, poor coordination with the owner, work safety regulations, wrong or incomplete designs, lack of contractor supervision of subcontractors, decreased quality of workers There are 11 priority treatment strategies. The priority of the handling strategy is securing the project location, choosing a competent PM, imposing sanctions on those who violate it, making working drawings, holding frequent meetings, making work implementation schedules, changing work methods to make them faster, accelerating resource procurement, monitoring the performance of subcontractors, implementing K3, and the stock of materials is multiplied.